2013
DOI: 10.1002/hon.2044
|View full text |Cite
|
Sign up to set email alerts
|

Emerging roles of endoglin/CD105 and angiogenic cytokines for disease development and progression in multiple myeloma patients

Abstract: Angiogenesis is an essential process for the expansion of multiple myeloma (MM), in which many angiogenic factors participate. Endoglin (CD105) is a transforming growth factor-β co-receptor, being mainly expressed in angiogenic endothelial cells and has been used as a marker of tumor angiogenesis, having prognostic potential. The aim of the study was to evaluate serum levels of soluble CD105 (sCD105) in MM patients, both during diagnosis and after effective conventional chemotherapy, in the plateau phase, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…[39] Both myeloma cell lines and primary cells were shown to express TGF-β mRNA and active protein, [40,41] however it was also reported that myeloma cells do not produce active TGF- Expression of the other type 3 receptor, endoglin, is induced by TGF-β and hypoxia, [44,45] and increased levels of soluble endoglin in myeloma patients were associated with advanced disease and tumor growth. [46,47] Membrane-bound endoglin is found on some myeloma cell lines, but lack on others. [35] Expression of selected receptors and their putative ligands in myeloma cells is summarized in Table 1.…”
Section: Expression Of Related Receptors and Ligandsmentioning
confidence: 99%
“…[39] Both myeloma cell lines and primary cells were shown to express TGF-β mRNA and active protein, [40,41] however it was also reported that myeloma cells do not produce active TGF- Expression of the other type 3 receptor, endoglin, is induced by TGF-β and hypoxia, [44,45] and increased levels of soluble endoglin in myeloma patients were associated with advanced disease and tumor growth. [46,47] Membrane-bound endoglin is found on some myeloma cell lines, but lack on others. [35] Expression of selected receptors and their putative ligands in myeloma cells is summarized in Table 1.…”
Section: Expression Of Related Receptors and Ligandsmentioning
confidence: 99%
“…31, 32, 33 It was reported that serum levels of endoglin were higher in multiple myeloma patients than in healthy controls and that high levels were associated with advanced disease, tumor growth and angiogenesis. 34, 35 …”
Section: Introductionmentioning
confidence: 99%
“…Following ACL-R surgery, the biological events within the knee joint tissue are similar to those observed during wound healing. Recent studies have shown that endoglin (CD105) is a TGFb co-receptor and marker of tumor angiogenesis [39]. Angiogenesis is also essential for repair processes and the increased fibrosis observed in the IPFP tissue following ACL-R surgery could be partially attributed to the interplay of these two biologically relevant molecules.…”
Section: Discussionmentioning
confidence: 99%